2013
DOI: 10.1126/science.1241460
|View full text |Cite
|
Sign up to set email alerts
|

Probing the Limits of Genetic Recoding in Essential Genes

Abstract: Engineering radically altered genetic codes will allow for genomically recoded organisms that have expanded chemical capabilities and are isolated from nature. We have previously reassigned the translation function of the UAG stop codon; however, reassigning sense codons poses a greater challenge because such codons are more prevalent, and their usage regulates gene expression in ways that are difficult to predict. To assess the feasibility of radically altering the genetic code, we selected a panel of 42 high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
157
1
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 125 publications
(162 citation statements)
references
References 37 publications
2
157
1
2
Order By: Relevance
“…Three of the N-terminal failures (ssb_AGA10, dnaT_AGA10, and prfB_AGG64) had RBS-like motifs that were either disrupted or created by CGU replacement. Although prfB_AGG64 is part of the RBS motif that triggers an essential frameshift mutation in prfB (21,38,39), pausing motifmediated regulation of ssb and dnaT expression has not been reported. Nevertheless, ribosomal pausing data (20) showed that ribosomal occupancy peaks are present directly downstream of the AGR codons for ssb and are absent for dnaT (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Three of the N-terminal failures (ssb_AGA10, dnaT_AGA10, and prfB_AGG64) had RBS-like motifs that were either disrupted or created by CGU replacement. Although prfB_AGG64 is part of the RBS motif that triggers an essential frameshift mutation in prfB (21,38,39), pausing motifmediated regulation of ssb and dnaT expression has not been reported. Nevertheless, ribosomal pausing data (20) showed that ribosomal occupancy peaks are present directly downstream of the AGR codons for ssb and are absent for dnaT (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Although Quax et al (18) provide an excellent review of how biology chooses codons, systematic and exhaustive studies of codon choice in whole genomes are lacking. Studies have only begun to probe the effects of codon choice empirically in a relatively small number of reporter genes (12,(19)(20)(21)(22). Several important questions must be answered as a first step toward designing custom genomes exhibiting new functions: How flexible is genomewide codon choice?…”
mentioning
confidence: 99%
“…Whenever the drive is copied, the cut gene is replaced with a recoded version flanked by the other components of the drive. Recent work has demonstrated that most genes can be substantially recoded with little effect on organism fitness 93 ; the 3' untranslated region might be replaced with an equivalent sequence from a related gene. Because there would be no homology between the recoded cut site and the drive components, the drive cassette would always be copied as a unit.…”
Section: Evolutionary Stabilitymentioning
confidence: 99%
“…Recoding is not permitted within the first 100 bp of each ORF, as these regions are known to have special preferences in terms of codon usage 7 . Together, these design rules favor high performance of almost all PCRTags under a single set of PCR conditions whereby synthetic and wild type PCRTag primer pairs exclusively bind and amplify synthetic and native DNA, respectively ( Figure 1B).…”
Section: Introductionmentioning
confidence: 99%